A review on resistance spot welding of magnesium alloys. Issue 5 (September 2016) - Manladan, S.; Yusof, F.; Ramesh, S.; Fadzil, M.
Abstract This paper presents a review on resistance spot welding of magnesium alloys, with emphasis on the relationship between microstructure, properties, and performance, under quasi-static and dynamic loading conditions. It also compares the resistance spot welding of magnesium-to-aluminum alloys and the various techniques used to suppress the formation of brittle intermetallic compounds. Resistance spot welding of magnesium-to-steel, weld bonding, the effects of process parameters on joint quality, and the main metallurgical defects in resistance spot welding of magnesium alloys are also deliberated. Studies have shown that the pre-existence of coarse second phase particles in the base metal, the addition of particles, such as titanium powder, and welding under the influence of electromagnetic stirring effect can promote columnar-to-equiaxed transition, microstructure refinement, and improvement in mechanical properties of magnesium alloys resistance spot welds. For magnesium-to-aluminum alloys spot welds, the use of interlayers, such as pure nickel, gold-coated nickel foil, and zinc-coated steel, was found to suppress the formation of brittle intermetallic compounds and thus significantly improve the joint strength.